Corneal and Epidermal Nerve Quantification in Chemotherapy Induced Peripheral Neuropathy - Riva, Nilo; Bonelli, Filippo; Lasagni Vitar, Romina Mayra; Barbariga, Marco; Fonteyne, Philippe; Lopez, Ignazio Diego; Domi, Teuta; Scarpa, Fabio; Ruggeri, Alfredo; Reni, Michele; Marcatti, Magda; Quattrini, Angelo; et al. (Frontiers in Medicine, 2022)
Chemotherapy-induced neurotoxicity is an increasingly recognized clinical issue in oncology. In vivo confocal microscopy (IVCM) of corneal nerves has been successfully used to diagnose peripheral neuropathies, including diabetic neuropathy. The purpose of this study was to test if the combination of corneal nerve density and morphology assessed by IVCM is useful to monitor the neurotoxic effects of chemotherapy compared to epidermal nerve quantification. Overall, ninety-five adult patients with different cancer types were recruited from the oncology and hematology departments of the San Raffaele Hospital. Neurological examination, including Total Neuropathy Score, and in vivo corneal confocal microscopy (IVCM), were performed before and after chemotherapy. In a group of 14 patients, skin biopsy was performed at the first and last visit. In the group of 14 patients who underwent both skin biopsy and corneal nerve imaging, clinical worsening (+69%, p=0.0018) was paralleled by corneal nerve fiber (CNF) density reduction (-22%, p=0.0457). Total neuropathy score significantly worsened from the first to the last visit (+62%, p<0.0001). CNF density was not significantly reduced overall. However, CNF density/tortuosity ratio significantly decreased after therapy. Correlation analysis showed that the CNF density/tortuosity ratio was also correlated with the number of chemotherapy cycles (r= -0.04790, P=0.0009). Our data confirm that in vivo corneal confocal microscopy is a helpful, non-invasive tool to diagnose chemotherapy-induced peripheral neuropathies. IVCM could allow a rapid, reproducible and non-invasive quantification of peripheral nerve pathology in chemotherapy-associated neuropathy.